Відтворення основних форм власності – необхідна умова створення сучасної держави Україна - Кузьменко, Леонід Володимирович (НТУ "ХПІ", 2015)
У статті на основі системного підходу охарактеризовані основні форми власності як базові інститути економічної системи суспільства, проведено аналіз причинно-наслідкових зв’язків між перетвореннями у відносинах власності та соціально-економічним станом України за останні два з половиною десятиріччя, відмічено актуальні проблеми відтворення відносин власності впроцесі побудови держави Україна.

On the basis of a systematic approach characterized the main form of ownership as the basic institutions of the economic system of the society, the analysis of causality between changes in the ownership relations and socio-economic situation in Ukraine over the past two and a half decades, marked urgent problems of reproduction of property relations in the process of building the state of Ukraine. It was found that the mixed ownership in the most contemporary answers to bend as globalization, the comprehensive development of man as a decisive factor of production, the task of building a modern state of Ukraine.
The reproduction of the main forms of property - a necessary condition for the creation of the modern state of Ukraine
Keywords: економічний стан країни; відносини власності; колективна власність; олігархічний капіталізм; змішана власність; приватизація; державна власність